Influence of age and geographical origin in the prevalence of high risk human papillomavirus in migrant female sex workers in Spain. Issue 1 (28th January 2005) - del Amo, J; González, C; Losana, J; Clavo, P; Muñoz, L; Ballesteros, J; García-Saiz, A; Belza, M J; Ortiz, M; Menéndez, B; del Romero, J; Bolumar, F
Abstract : Objectives: To estimate the prevalence and risk factors of high risk human papillomavirus (HPV) infection in migrant female sex workers (FSW) according to age and geographical origin. Methods: Cross sectional study of migrant FSW attending a sexually transmitted infection (STI) clinic in Madrid during 2002. Information on sociodemographic characteristics, reproductive and sexual health, smoking, time in commercial sex work, history of STIs, HIV, hepatitis B, hepatitis C, syphilis, and genitourinary infections was collected. High risk HPV Infection was determined through the Digene HPV Test, Hybrid Capture II. Data were analysed through multiple logistic regression. Results: 734 women were studied. Overall HPV prevalence was 39%; 61% in eastern Europeans, 42% in Ecuadorians, 39% in Colombians, 29% in sub-Saharan Africans, and 24% in Caribbeans (p = 0.057). HPV prevalence showed a decreasing trend by age; 49% under 20 years, 35% in 21–25 years, 14% over 36 years% (p<0.005). In multivariate analyses, area of origin (p = 0.07), hormonal contraception in women not using condoms (OR 19.45 95% CI: 2.45 to 154.27), smoking, age, and an interaction between these last two variables (p = 0.039) had statistically significant associations with HPV prevalence. STI prevalence was 11% and was not related to age or geographical origin. Conclusions: High risk HPV prevalence in migrant FSW is elevated and related to age, area of origin, and use of oral contraceptives in women not using condoms. These data support the role of acquired immunity in the epidemiology of HPV infection and identifies migrant FSW as a priority group for sexual health promotion.